Chlorella vulgaris reduces the impact of stress on hypothalamic–pituitary–adrenal axis and brain c-fos expression. (March 2016) - Souza Queiroz, Julia; Marín Blasco, Ignacio; Gagliano, Humberto; Daviu, Nuria; Gómez Román, Almudena; Belda, Xavier; Carrasco, Javier; Rocha, Michelle C.; Palermo Neto, João; Armario, Antonio
Highlights: Acute pretreatment with C. vulgaris reduced stress-induced HPA activation (ACTH levels and hnCRF expression in the PVN). Acute pretreatment with C. vulgaris reduced stress-induced c- fos expression in most evaluated brain regions. Acute pretreatment with C. vulgaris reduced stress-induced hyperglycemia. Abstract: Predominantly emotional stressors activate a wide range of brain areas, as revealed by the expression of immediate early genes, such as c- fos . Chlorella vulgaris (CV) is considered a biological response modifier, as demonstrated by its protective activities against infections, tumors and stress. We evaluated the effect of acute pretreatment with CV on the peripheral and central responses to forced swimming stress in adult male rats. Pretreatment with CV produced a significant reduction of stress-related hypothalamic–pituitary–adrenal activation, demonstrated by decreased corticotrophin releasing factor gene expression in the hypothalamic paraventricular nucleus (PVN) and lower ACTH response. Hyperglycemia induced by the stressor was similarly reduced. This attenuated neuroendocrine response to stress occurred in parallel with a diminished c- fos expression in most evaluated areas, including the PVN. The data presented in this study reinforce the usefulness of CV to diminish the impact of stressors, by reducing the HPA response. Although our results suggest a central effect of CV, further studies are necessary to understand the precise mechanisms underpinning this effect.